Iron–Nutrient Interactions within Phytoplankton - Schoffman, Hanan; Lis, Hagar; Shaked, Yeala; Keren, Nir (Frontiers in Plant Science, 2016)
Iron limits photosynthetic activity in up to one third of the world’s oceans and in many fresh water environments. When studying the effects of Fe limitation on phytoplankton or their adaptation to low Fe environments, we must take into account the numerous cellular processes within which this micronutrient plays a central role. Due to its flexible redox chemistry, Fe is indispensable in enzymatic catalysis and electron transfer reactions and is therefore closely linked to the acquisition, assimilation and utilization of essential resources. Iron limitation will therefore influence a wide range of metabolic pathways within phytoplankton, most prominently photosynthesis. In this review we map out four well-studied interactions between Fe and essential resources: nitrogen, manganese, copper and light. Data was compiled from both field and laboratory studies to shed light on larger scale questions such as the connection between metabolic pathways and ambient iron levels and the biogeographical distribution of phytoplankton species.